2021
DOI: 10.1080/03098265.2021.1986687
|View full text |Cite
|
Sign up to set email alerts
|

Lockdown lessons: an international conversation on resilient GI science teaching

Abstract: We report the findings from two global panel "conversations" that, stimulated by the exceptional coronavirus pandemic of 2020/21, explored the concept of resilience in geographic science teaching and learning. Characteristics of resilient teaching, both in general and with reference to GISc, are listed and shown to be essentially what might in the past have been called good teaching. Similarly, barriers to resilient teaching are explored and strategies for overcoming them listed. Perhaps the most important con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…The COVID-19 pandemic disrupted HE profoundly. A series of lockdowns required university staff to rapidly adapt their practices to digital online spaces (Crawford et al, 2020;Blanford, 2022). For many academic staff, this involved a move away from long-established campus-based pedagogic norms, requiring them to rethink and adapt their practice quickly (Hodges et al, 2020).…”
Section: The Impact Of Covid-19 Disruption On Higher Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…The COVID-19 pandemic disrupted HE profoundly. A series of lockdowns required university staff to rapidly adapt their practices to digital online spaces (Crawford et al, 2020;Blanford, 2022). For many academic staff, this involved a move away from long-established campus-based pedagogic norms, requiring them to rethink and adapt their practice quickly (Hodges et al, 2020).…”
Section: The Impact Of Covid-19 Disruption On Higher Educationmentioning
confidence: 99%
“…Little research, however, has focused on university teaching staff and even less appears to consider professional services staff. Arguably, academic and professional services staff are accustomed to adopting new ways of working in line with changes to policy and practice (Dulohery et al, 2021) but with the pandemic, the speed of change was unprecedented (Blanford, 2022). Watermeyer et al (2021) suggested that COVID-19 engendered "significant dysfunctionality and disturbance to … pedagogical roles and … personal lives" (p. 623), which could be disorienting for university academics.…”
Section: The Impact Of Covid-19 Disruption On Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous works on GIS BoKs mainly focus on curriculum design (Blanford et al, 2022; DeMers, 2019; Elwood & Wilson, 2017; Hossain & Reinhardt, 2012; Johnson & Sullivan, 2010; Kemp, 2012; Prager, 2012) and skill identification (Hong, 2016; Johnson, 2019; Sadvari, 2019; Wallentin et al, 2015). Only a few semantic analysis works have been conducted to understand geospatial domain knowledge and essential terminologies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Schultz and DeMers (2020) called for a transition from what they called 'emergency remote learning' to further develop and prepare online learning experiences. When teaching ceases to be necessarily online, Blanford et al (2022) argued that it should not simply return to a traditional learning system as developed before but should build on the experiences during the pandemic to move towards a learning practice that benefits from new technologies in geography teaching, which should be made compatible with face-to-face and hybrid education. If applied well, learning tools experimented with during the pandemic can complement face-to-face practices and optimize lessons time; a good example is the implementation of virtual field trips for the teaching of geography (Geraghty & Kerski, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%